Multi-material forging of lightweight materials - Ong, Jeremy Wei Song (2017)
Going lightweight and yet retaining the strength of products have been the trend in the manufacturing industry in recent years. The current industry does not yet have a single process for forming and joining, and not to mention that there are very few methods in terms of optimizing strength-to-weight ratio. Processes such as welding or riveting are examples of a joining procedure to join similar or dissimilar materials together. However, such processes often take up extra time and costs due to the extra joining step required. As a result, a new “joining by forming” manufacturing process, multi-material forging of lightweight materials, was introduced. This project examines the soundness of multi-material forging of steel and aluminium, as well as to investigate the parameters governing the effectiveness of a multi-material forged specimen. Simulations and mechanical testing, such as hardness test and push-out test, are done to determine the quality of material bonding, combinations of material selection and process parameters. Experiments concluded that a multi-material forged specimen weighed 14% lighter and was able to withstand loading of up to 83.6% higher than a single-material forged specimen. Hardness testing concluded with the possibility of presence of residual stress at the joint area, before simulations ran with DEFORMTM confirmed the presence of residual stress within the bond. Future works will include designs of marketable multi-material products that can be mass produced and exploring different types of material combinations.